Diversity of Postharvest pathogenic fungi of green bean pods in Egypt - Ali, I. N. M.,; El-Nabi, H. M.,; Khalil, M. I. I,; El-Gamal, Nadia, G.,; EL-Mohamedy, R. S. R.,; Abd El-kareem, F.,; Khalil, M. S. A., (International Journal of Agricultural Technology, 2016)
In Egypt, rot disease of green bean pods (Phaseolus vulgaris. L) is the major problem during storage and marketing. Sclerotinia sclerotiorum andBotrytis cinerea were most dominant fungi followed by Alternaria sp., R. solani and Fusarium sp. Sclerotinia sclerotiorum was the most dominate fungi isolated from rotted pods collected from different markets in Egypt. All the tested fungi were able to infect pods of green bean Valintino Cultivare. The highest records of disease infection (80 and 75.6 %) on green bean pods were found with two isolates of S. sclrotiorum (Sc 11 and 13). But the two isolates of Botrytis cinerea isolate 2, 1 and 3 show moderate disease incidence .Meanwhile, other isolated fungi cause the least records of rot disease incidence on faba bean pods. Physiological studies Cleary show that there is a variation among tested isolates of S. sclerotiorum according to pathogenic ability, linear growth, the number and size of sclerotia .